2002
DOI: 10.1177/0895904802016004010
|View full text |Cite
|
Sign up to set email alerts
|

Community College Puente: A Validating model of Education

Abstract: Employing Rendón’s theory of validation, the validating elements in Community College Puente are identified. Implications for promoting access, use of involvement and validation theory, and employment of learning theory for nontraditional student populations are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
153
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(162 citation statements)
references
References 14 publications
8
153
0
1
Order By: Relevance
“…Chang's (2005) Islander and Latino students were especially low. The findings of the study were consistent with past research (Braxton, Hirachy, & McClendon, 2004;Rendón, 2002) that has shown faculty-student interaction to positively influence a number of student outcomes and be of particular benefit to the academic achievement and persistence of students of color.…”
Section: Persistence Among Nontraditional Community College Studentssupporting
confidence: 81%
See 3 more Smart Citations
“…Chang's (2005) Islander and Latino students were especially low. The findings of the study were consistent with past research (Braxton, Hirachy, & McClendon, 2004;Rendón, 2002) that has shown faculty-student interaction to positively influence a number of student outcomes and be of particular benefit to the academic achievement and persistence of students of color.…”
Section: Persistence Among Nontraditional Community College Studentssupporting
confidence: 81%
“…The research suggests that for language-minority students, motivation for attending and succeeding in college may differ greatly from their White American peers (Guiffrida, 2006;Rendón, 2002;Stage, 1989). Their goals, intentions, and motivation for academic success is determined by individual, yet characteristic, factors particular to this subgroup of minority students.…”
Section: Persistence Among Language-minority Community College Studentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Like all postsecondary students, Latinx community college transfer students benefit from support, caring, and validation from institutional agents who can further support their educational experiences (Dowd, Pak, & Bensimon, 2013;Rendón, 2002). Dowd et 1 Our use of Latinx is an attempt at inclusivity and recognition of the non-binary, trans*, and fluid nature of gender-as well as the continuous development of language and linguistic choices.…”
Section: Introductionmentioning
confidence: 99%